Pengelolaan Keuangan di Desa Pesisir Berdasarkan Asas Partisipasi dalam Undang Nomor 6 Tahun 2014 Tentang Desa sebagai Upaya Akuntabilitas Publik di Kabupaten Gresik - Chomariyah (Faculty of Law Hang Tuah University, 2015)
The financial management in the coastal villages based on the principle of public participation is regulated in Act Number 6 of 2014 on the Village. The regulating is intended that rural communities can participate and play the role and can directly involve in financial management, including the supervision on financial allocations. The selected coastal villages in Gresik are Pangkah Kulon village, Banyu Urip village and Campurejo village; the villages are in two sub-districts (kecamatan), Ujung Pangkah and Panceng. This research is an empirical research with the steps which refer to the principle of PAR (Participatory Action Research). The research advances show that the location of the research and the regulations have been identified; the informants have been determined; and the data on Village Fund Allocation and the model of village financial management of which each village makes have been collected. As a result of the research, the model of financial management in Pangkah Kulon village, Banyu Urip village and Campurejo village is not maximally in accordance with the steps that should be as in the regulations, particularly in the Regulation of the Minister of Home Affairs Number 113 of 2014 on Village Financial Management. The used format is not uniform.